TENSES UNDERSTANDING IN USING THE ENGLISH LANGUAGE - Martina Napratilora; Seri Yanti Siagian (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2019)
Language is one of the tools for communicating. English is one of the languages that are used to communicate. Mastering simple present tense is able to make English communicating run well, effectively, and clearly. Using the English language to communicate in daily life should comprehend about simple present tense because this tense more often to be used than other tenses for daily communication. This paper will explain how to make sentences using simple present and how to use simple present in communicating. Simple present tense refers to something happened in present time. The students will be easy to understand and use tense by knowing who the subject in the sentence is, knowing the sentence kinds, and knowing the sentence form.